Elastic Design Charts for the Rapid Selection of Web Bolts for Composite Steel Bridge Splices - Sheikh-Ibrahim, Firas I. (Engineering Journal, 2002)
Selection of the web bolts for steel bridge girder splices requires a trial and error procedure. A group of bolts is initially selected, and its resistance is checked against the required resistance. If the provided resistance is less than required, a new group of bolts is selected and the procedure is repeated until an acceptable design is achieved. In this paper, elastic design charts for the rapid selection of web bolts are presented along with three design examples. The charts are developed to be used for composite bridge girder splices at either the strength limit state or the service limit state, but can be used for any other eccentric shear connection. The charts can be used for connections with bolted depths ranging from 900 mm to 2000 mm, eccentricity-to-bolted-depth ratios up to 1.5, design forces applied at 0° to 80° from the vertical axis, a uniform vertical bolt spacing, and a horizontal bolt spacing of 75 mm. The required bolt pattern can be determined directly from the charts for a known bolted depth, eccentricity, vertical design shear, angle of the design force line of action, and factored resistance of one bolt.